2017
DOI: 10.1186/s12887-017-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Universal versus conditional three-day follow up visit for children with uncomplicated fever at the community level: design of a cluster-randomized, community-based, non-inferiority trial in Tanganyika, Democratic Republic of Congo

Abstract: BackgroundThe current recommendation within integrated Community Case Management guidelines that all children presenting with uncomplicated fever and no danger signs be followed up after three days may not be necessary. Such fevers often resolve rapidly (usually within 48–96 h), and previous studies suggest that expectant home care for uncomplicated fever can be safely recommended. We aim to determine the non-inferiority of a conditional versus a universal follow-up visit for these children.MethodsWe are condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Further details of our cluster-randomized non-inferiority trial have been published elsewhere [ 16 ]. Briefly, each of the 28 health areas (14 in each zone) consisted of a health center and a team of 1 to 18 associated CHWs: literate, locally resident volunteers who received 5 days of training on the iCCM algorithm and other core competencies (e.g., communication and recording) as per DRC Ministry of Public Health guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of our cluster-randomized non-inferiority trial have been published elsewhere [ 16 ]. Briefly, each of the 28 health areas (14 in each zone) consisted of a health center and a team of 1 to 18 associated CHWs: literate, locally resident volunteers who received 5 days of training on the iCCM algorithm and other core competencies (e.g., communication and recording) as per DRC Ministry of Public Health guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…We used restricted randomization balanced on zone and health area estimates of (1) population size, (2) prior 6-month likelihood of mRDT-negative febrile children (number of children mRDT negative/under-5 population), and (3) geographic distance from CHW to zonal health center to allocate the 28 health areas (and all the CHWs and the children they enrolled within these areas) to either universal or conditional follow-up advice (also see sample size section below) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still not enough evidence globally that payment of community health workers (CHWs) will resolve the issue of motivation and retention and further research on these areas is needed. In interviews conducted as part of another research study [24] with RECOs in other health zones in the region, many RECOs noted that their work takes up a great deal of time, largely due to the number of tools required to complete, leaving them with limited time for their income-generating activities. Other studies have also found that RECOs are frustrated and confused by complex tools and protocols [8] and Guenther et al [25] have pointed out that complexity also reduces the quality of data and its utility for program improvement.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for this, we will address this issue during interviews, as well as on pilot testing of the interview guides, to ensure that any gender-related issues will be prevented. This study, along with a sister study in Democratic Republic of Congo [ 27 ], is the only study designed to look at this critical policy issue. It therefore has high potential to contribute to the knowledge base by assessing and evaluating recommended practices for treating febrile children whose illness cannot be diagnosed at the community level using iCCM guidelines.…”
Section: Discussionmentioning
confidence: 99%